1980
DOI: 10.1007/bf00016527
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of water molds in relation to hydrogen ion concentration in some lakes of Nainital, India

Abstract: 26 species of water molds belonging to Blastocladiales, Saprolegniales, Lagenidiales and Peronosporales were found to be different in their pH tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Moreover. KHULBE (1980) found that most of water moulds are able to tolerate a wide range of pH and some of them do not tolerate pH value less than 7.5. The water temperature of the investigated samples at the time of sampling was relatively low to moderate and ranged between 11.0-25.0 ' C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover. KHULBE (1980) found that most of water moulds are able to tolerate a wide range of pH and some of them do not tolerate pH value less than 7.5. The water temperature of the investigated samples at the time of sampling was relatively low to moderate and ranged between 11.0-25.0 ' C .…”
Section: Resultsmentioning
confidence: 99%
“…COKER 1923, SPARROW 1958, DAYAL and THAKURJI 1966, EL-HISSY 1974, 1979a, b, LUI and VOLZ 1976, ZEBROWSKA 1976, Fox and WOLF 1977. KHULBE 1980, RATTAN et al 1980, DEACON 198 1, EL-HISSY et al 1982, KLICH and TIFFANY 1985, EL-HISSY and KHALLIL 1989 and others).…”
mentioning
confidence: 99%
“…There is no general consensus among different workers about the cause of fluctuations in species content of watermolds. Different workers have attributed seasonal fluctuations to different causes such as pH (LUND 1943;WOLF and WOLF 1941;SUZUKI 1960;DAYAL and TANDON 1963;SRIVASTAVA 1967;KHULBE 1980) MER et al 1980). In the present study, fourteen species of watermolds were restricted to terrestrial and seven species to aquatic habitats while eleven species were common in both the systems.…”
Section: Discussionmentioning
confidence: 99%
“…Also, SUZUKI (1961) indicated that zoosporic fungi were very scarce or absent in acidotrophic lakes (pH 1.90 -2.75) and in pH 2.9 -5.8 one or more fungi were recovered. KHULBE (1980) classified water moulds into three groups: with a wide range of pH tolerance (7.3-8.8), with a moderate range (7.4-8.2) and with a narrow range of pH tolerance (7.3 -7.7). DAYAL and TANDON (1963) found a maximum number of water moulds in a pond having pH 6.9 -7.0.…”
Section: Water Samplesmentioning
confidence: 99%